2013
DOI: 10.4236/ojn.2013.36060
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed obstructive sleep apnea in hypertensive outpatients in primary care—Associations with sleep complaints, depressive symptoms and global perceived health

Abstract: Objective: 1) To describe the prevalence of undiagnosed obstructive sleep apnea (OSA) and depressive symptoms in hypertensive men and women below 65 years of age, and 2) to describe the association of OSA to subjective sleep complaints, depressive symptoms and global perceived health. Design: Cross-sectional design focusing on nursing care outcomes of obstructtive sleep apnea. Setting: Four primary care health centres in Sweden. PATIENTS: 411 consecutive patients (52% women), mean age 57.9 years (SD 5.9 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…and daytime sleepiness, all of which are linked to OSA among individuals referred to the sleep clinics. 6,7 These factors also contribute to decreases the health perceptions in the general population. 6 Stress is a substantial influence impacting various dimensions of both physical and mental well-being in contemporary society.…”
Section: Original Articlementioning
confidence: 99%
See 1 more Smart Citation
“…and daytime sleepiness, all of which are linked to OSA among individuals referred to the sleep clinics. 6,7 These factors also contribute to decreases the health perceptions in the general population. 6 Stress is a substantial influence impacting various dimensions of both physical and mental well-being in contemporary society.…”
Section: Original Articlementioning
confidence: 99%
“…6,7 These factors also contribute to decreases the health perceptions in the general population. 6 Stress is a substantial influence impacting various dimensions of both physical and mental well-being in contemporary society. Specifically, "perceived stress," referring to a person's personal evaluation of their stress levels over a certain timeframe, can be influenced by a person's life experiences, physical and mental health, and social support, among other factors.…”
Section: Original Articlementioning
confidence: 99%
“… 19 Broström et al found that undiagnosed mild and moderate/severe OSA was seen among 29% and 30% of patients with HTN, respectively. 20–22 The current guidelines by US Preventive Services Task Force (USPSTF) do not recommend any screening for OSA in asymptomatic patients due to insufficient research and data. 1–4 …”
Section: Introductionmentioning
confidence: 99%
“…Not only systemic hypertension, but also pulmonary hypertension, heart failure, arrhythmia, stroke, and myocardial infarction can be observed. All these situations increase morbidity and mortality related to OSAS [4][5].…”
Section: Introductionmentioning
confidence: 99%